THE EFFECT OF ADMINISTRATIVE SERVICES TOWARDS STUDENTS’ SATISFACTION IN BUANA PERJUANGAN KARAWANG UNIVERSITY - Firmansyah, Yudi; Isyanto, Puji; Haizam Mohd Saudi, Mohd (International Journal of Psychosocial Rehabilitation, 2020)
Employee performance and service quality of academic administration and influential with students’ satisfaction. The better the performance of employees and service quality the better the administration of student assessment. On the other hand, there are still beberpa issues relating to it. As their class schedule that collision, making the length of the required letters, do not miss the eyes of college classes, their names are not listed diabsensi. This study intended to answer these problems. Third relations employee performance and service quality of the academic administration of the student satisfaction., Recognizing the importance of this, then do research with the aim to determine the effect of the quality of academic and administrative services to the satisfaction of UBP FEB students simultaneously and partially using associative method. The study population was a student FEB. method of research used a qualitative approach.